Exploring settler innocence among early childhood educators in the Osage community: a case study - Hall, Joni (Kansas State University, 2022)
The purpose of this revelatory case study was to better understand the curricular decision-making processes of early childhood teachers teaching pre-kindergarten through third grade when constructing learning environments related to Indigenous peoples and cultures in selected public schools in Osage County, Oklahoma. Specifically, this study explored early childhood education teacher unit and lesson planning, as well as perceptions related to confidence, preparedness, and effectiveness when creating learning environments about, with, and for Indigenous peoples and cultures. This study was guided by the theoretical frameworks of settler innocence (Lees et al., 2021), perceived self-efficacy (Bandura, 2012), and Liberating Sovereign Potential (RedCorn, 2020), which centered the role of Osage sovereignty. Community based qualitative research (Johnson, 2017) was also used as an underpinning to guide this study. This study analyzed the perceptions of individual early childhood teachers working across 13 school districts, of which 12 schools were Osage Reservation/Osage County Johnson O’Malley (JOM) site schools. An inductive approach was used to analyze the data collected through semi-structured interviews, questionnaires, and document collection. First and second cycle coding, discourse analysis, and document analysis were used to understand the themes that emerged from the research questions. Findings showed that access barriers within the school influenced teachers’ perceptions of confidence, preparedness, and effectiveness to make decisions related to Native peoples and cultures in their classrooms. Findings also showed that teachers were able to identify what they need to be able to teach Native cultural content and create learning environments that support Native children and cultures. The findings from this study can be used to inform future Indigenous educational decision-making specific to early childhood curriculum and teacher development as it relates to Osage and other Indigenous contexts at the teacher level, policy level, and tribal government level.
Keywords: Indigenous; Osage; Early childhood; Public school; Early childhood teacher